Dormancy and cardinal temperatures during seed germination of five weedy rice (Oryza spp.) strains - Adam, Puteh; Roziah, Rosli; Rosli, Mohamad (Universiti Putra Malaysia Press, 2010)
Temperature during seed imbibition has been found to influence germination rate and final percent germination. Seeds of one cultivated variety and five weedy rice strains, collected from different localities in Peninsular Malaysia, were used to determine their degree of dormancy and cardinal temperatures. Meanwhile, standard germination and tetrazolium chloride (TTC) tests were used to evaluate the percentage of seed viability and degree of dormancy. Seed germination test at six different constant temperatures (between 10 and 35oC) was applied to determine the cardinal temperatures estimated by linear regression models, base temperature, Tb, optimum temperature, To, and maximum temperature, Tc. The TTC test was found to be a simple and quick test to determine the degree of seed dormancy among different weedy rice strains, when used together with a standard germination test. Germination rate was found to be related to the degree of dormancy but it had no influence on the range of cardinal temperatures. The Tb among the five weedy rice strains was in the range of 2-7.3oC. The To varied between 28.1 and 37.5oC, with an average of 32.5oC. This temperature (To) was higher than that of the cultivated MR73 variety (24.3oC), whereas the range of Tc was 42.2-43.3oC. The study indicated that the non-dormant cultivated rice seed had lower Tb and To values than the dormant seed of weedy rice.